STUDI PENGARUH KONDISI WETTING DAN DRYING BIOFILTER UNTUK PENYISIHAN LOGAM BERAT DAN TOTAL SUSPENDED SOLID (TSS) PADA URBAN STORMWATER - Purnama Dewi, Wulan
Pollutans in urban stormwater or runoff from urban street, particulary in Dago-Bandung contain of organic matter, heavy metals and total suspended solid (TSS). Heavy metals, especially copper (Cu) and zinc (Zn) and total suspended solid (TSS) are the focus parameters of this research. The objectives of this study are to determine the effect of wetting and drying biofilter conditions as the simulation of natural conditions related to the erratically time of rainfall toward Cu, Zn, and total suspended solid (TSS) removal in urban stormwater and to know when pollutants can be removed properly. Filter media that used in biofilter are coarse gravel, fine gravel, sand, and mixture of soil and compost were planted Vetiveria zizanioides (L.) Nash. Wetting and drying variations that used are long period of wetting and drying; random period of wetting and drying; and the regular alternating period of wetting and drying. Influent discharge of urban stormwater 0.51 liters/min for 25 minutes. Urban stormwater has pH between 6.7 to 8.24 and decreased after treated in a biofilter to 5.78 to 7.4. Soil moisture continued to increase during wet periods and decreased during dry periods ongoing. Alternation of wetting and drying conditions has a significant influence on the removal efficiency of total suspended solid (TSS), which continued to increase during wet periods up to 100% and decreases when the dry period. And for Cu and Zn removal efficiency, the correlation and influence was not found significant of wetting and drying variations.